What doesn't kill her [large type] - Dodd, Christina (Wheeler Publishing, a part of Gale, a Cengage Company, 2019)
"Kellen Adams suffers from a yearlong gap in her memory. A bullet to the brain will cause that. But she's discovering the truth, and what she learns changes her life, her confidence, her very self. She finds herself in the wilderness, on the run, unprepared, her enemies unknown--and she is carrying a priceless burden she must protect at all costs. The consequences of failure would break her. And Kellen Adams does not break."--Amazon.